OP10 Comparative efficacy of biologics for endoscopic healing of the ileum and colon in Crohn's Disease. (21st January 2022) - Narula, N; Wong, E; Dulai, P; Marshall, J; Jairath, V; Reinisch, W
Abstract: Background: We compared the efficacy of adalimumab, infliximab, ustekinumab, and vedolizumab for achieving endoscopic healing (EH) in the ileum and colon after one-year of therapy in Crohn's disease (CD). Methods: A pooled analysis of patient-level data from 344 patients with CD from four clinical trial programs was performed. Patients who received continuous adalimumab, infliximab, ustekinumab, or vedolizumab throughout the trial and had at least one ileocolonic segment with a Simple Endoscopic Score for CD (SES-CD) ≥ 3 at enrolment were included. Proportions of patients achieving one-year endoscopic healing (EH), defined as SES-CD of 0, using each of four biologics were compared. Multivariate logistic regression was used to model the relationship between individual biologics and one-year outcomes, adjusted for potential confounders of EH, including disease duration, concomitant corticosteroid use, and prior anti-TNF failure. Results: Compared to vedolizumab [10/77 (13%)], both infliximab [29/79 (36.7%), aOR: 3.27 (95% CI: 1.34–8.01), p<0.001] and adalimumab [12/40 (30%), aOR: 3.01 (95% CI: 1.10–8.21), p=0.032] were superior for achieving one-year EH of the ileum among patients with ileal involvement at baseline. No difference was observed between ustekinumab [5/22 (22.7%)] and vedolizumab [aOR: 2.75 (95% CI: 0.76–9.91), p=0.123]. In biologic-naïve patients, ustekinumab, adalimumab, and infliximab were superior to vedolizumab for achieving one-year EH of the ileum. For colonic disease, in comparison to ustekinumab [9/31 (29.0%), adalimumab [30/48 (62.5%), aOR: 4.04 (95% CI: 1.88–8.71), p<0.001] and infliximab (55/105 (52.4%), aOR: 2.02 (95% CI: 1.03–3.99), p=0.041] were superior for one-year EH in the colon among patients with colonic involvements at baseline. No difference was seen between vedolizumab [26/87 (29.9%)] and ustekinumab [aOR: 1.01 (95% CI: 0.39–2.59), p=0.987]. Similar differences were noted among biologic-naïve patients. Conclusion: In this post-hoc analysis of pivotal clinical trials, TNFα antagonists were generally superior to vedolizumab and ustekinumab for achieving EH of the ileum and colon in patients with CD. However, among biologic-naïve patients, ustekinumab, adalimumab, and infliximab were superior to vedolizumab for attaining one-year EH of the ileum.